TECHNOLOGY OF CREATION OF POLYMER MATERIALS IN THE FORM WITH FUNGICIDAL PROPERTIES - KACHAN, ROMAN; TOLKACHOVA, ANASTASIA; KURIY, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Mycosis of the skin is a fungal disease that has been spreading rapidly recently. This is due to many factors: significant consumption of products with a high content of sugars, unreasonable intake of drugs with bactericidal properties, wearing clothes and shoes made of artificial materials that have unsatisfactory sanitary and hygienic properties. Mycosis of the feet has the property of further spreading to the nails. Mycosis of the feet is much easier to cure than mycosis of the nails - onychomycosis. Accordingly, when mycosis of the feet is detected, it is necessary to treat the feet and nails with an agent that will have a fungicidal effect on pathogenic fungi. Gels, creams, and ointments are most often used to treat mycosis of the skin of the feet. In terms of ease of use, gels are the most optimal form of the local remedy. When creating a polymer material in the form of a gel with fungicidal properties, active substances were used that were not previously used in antifungal agents. This minimizes the resistance of microflora to this agent. A cellulose derivative - hydroxyethyl cellulose - was used as a gelling agent. It provides high rheological and organoleptic properties. In order to promote the healing (scarring) of wounds caused by pathogens of mycosis, D-panthenol was used. It is necessary for the functioning of the epithelium. An increase in the need for this substance is observed in case of damage to the skin or other soft tissues of the body, and its deficiency can be replenished by local application of D-panthenol. Glycerin is used to moisturize the skin. The developed polymer agent in the form of a gel with fungicidal properties has the following composition: a mixture of four quaternary ammonium compounds (CA) - 0.1%; hydroxyethyl cellulose - 2.5%; glycerin – 1.0%; D - panthenol 75% in quantity - 1.2%; the water is prepared - the rest. It was established that this agent has pronounced fungicidal properties against the main pathogens of mycoses.